Nicotinamide Mononucleotide Restores the Meiotic Competency of Porcine Oocytes Exposed to Ethylene Glycol Butyl Ether - Miao, Yilong; Li, Xinyu; Shi, Xiaoyan; Gao, Qian; Chen, Jingyue; Wang, Rui; Fan, Yong; Xiong, Bo (Frontiers in Cell and Developmental Biology, 2021)
Ethylene glycol butyl ether (EGBE), a type of glycol ethers, is a common chemical used in both industrial and household products. Increasing animal studies have indicated that it produces reproductive problems, such as testicular damage, reduced female fertility, death of embryos and birth defects. However, how it influences the female germ cells has not yet determined. Here, we found that EGBE exposure resulted in the defective porcine oocyte maturation via disruption of cytoskeleton dynamics, showing the abnormal spindle assembly, chromosome alignment and actin organization. Meanwhile, EGBE exposure perturbed the mitochondrial distribution and function, leading to the accumulation of reactive oxygen species (ROS) and generation of DNA damage and apoptosis. Of note, nicotinamide mononucleotide (NMN) supplementation rescued the meiotic defects caused by EGBE exposure via restoring NAD+ level and mitochondrial function and thus eliminating the excessive ROS. Taken together, our observations illustrate that NMN supplementation is an effective strategy to protect oocyte quality against environmental pollutant-induced deterioration, contributing to improve the animal and human fertility.